A decade of pig genome sequencing: a window on pig domestication and evolution. Issue 1 (December 2016) - Groenen, Martien
Abstract Insight into how genomes change and adapt due to selection addresses key questions in evolutionary biology and in domestication of animals and plants by humans. In that regard, the pig and its close relatives found in Africa and Eurasia represent an excellent group of species that enables studies of the effect of both natural and human-mediated selection on the genome. The recent completion of the draft genome sequence of a domestic pig and the development of next-generation sequencing technology during the past decade have created unprecedented possibilities to address these questions in great detail. In this paper, I review recent whole-genome sequencing studies in the pig and closely-related species that provide insight into the demography, admixture and selection of these species and, in particular, how domestication and subsequent selection ofSus scrofa have shaped the genomes of these animals.